TEACHER’S PERCEPTION OF QUIZIZZ GAME-BASED LEARNING ON ADHD STUDENTS’ SPEAKING COMPETENCE AT AN-NUR ISLAMIC SCHOOL - Hikmah Lubis (Faculty of Tarbiyah nad Teacher Training, 2026)
This study aims to examine teachers' perceptions of using Quizizz as a game-based learning platform to improve the speaking skills of students with Attention Deficit Hyperactivity Disorder (ADHD) at An-Nur Islamic School. Speaking skills play a crucial role in English language learning; however, students with ADHD often face challenges in actively participating in speaking tasks. Game-based learning approaches, such as Quizizz, have been shown to enhance student motivation, engagement, and learning outcomes, especially for those who require more structure in their learning process. This qualitative case study explores the experiences and perceptions of English teachers in inclusive classrooms. The findings indicate that Quizizz’s gamification features, such as live mode, leaderboards, and instant feedback, effectively boost motivation and participation among ADHD students. Additionally, the use of Quizizz also improves various aspects of speaking skills, including fluency, vocabulary, and speaking confidence. However, the study also identifies technical and pedagogical challenges faced by teachers in using Quizizz, such as difficulty in finding suitable content and managing screen time for ADHD students. This research provides insights for developing more inclusive, technology-based speaking strategies for students with special needs.Keywords: Game-Based Learning, Quizizz, Speaking Skills